Socialization of Waste Management and Distribution of Trash Bins to Increase Community Knowledge in Kedungbako Village - Mita, Pramita; Laksmita Rachmawati, Dwita; Hastari, Sri (IJECS: Indonesian Journal of Empowerment and Community Services, 2025)
Waste is a crucial issue that must be addressed, especially by the government. Although waste is a particular concern, the reality is that it is not being managed properly. Waste remains an unresolved problem. Almost every day, people produce waste and it is mixed together from various types of waste. The accumulation of waste will cause various problems, such as flooding, ecosystem damage, and poor water sanitation. The purpose of this community service is to provide socialization about an effective waste management system, including the decomposition of organic and inorganic waste and the distribution of trash cans. Because the community service sees that one of the main factors that causes villagers to throw waste in the river is the lack of trash cans in several places frequently visited by the community. The method of implementing this PKM is initial implementation, socialization, distribution of trash cans, monitoring and evaluation with an emphasis on solving the problem, namely the lack of literacy and public awareness about waste. The conclusion of this community service is to create a clean environment free of waste that will have a positive impact on the community and the surrounding environment so that the community can realize the importance of managing waste that can generate economic value. It is hoped that this activity can increase and encourage public thinking about the benefits that can be generated by the presence of trash cans, waste management, and literacy that has been provided to the community.